Benchmarking - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT This article aims to develop an integral summary of the present status the model ("philosophy") of benchmarking. It includes the presentation o4 different bencmarking definitions, different benchmarking processm, preconditions for benchmarki& and finally, to propose an alternativj benchmarking model, processes of how to accomplish continuous improvement would be performed.